PENDAMPINGAN PEMBELAJARAN BIOLOGI ANATOMI HEWAN SECARA DARING UNTUK SEKOLAH-SEKOLAH DASAR GUGUS VI DI DESA TUKSONO, SENTOLO, KULON PROGO, YOGYAKARTA : Online Animal Anatomy Biology Learning Assistance for Cluster VI Elementary Schools in Tuksono Village, Sentolo, Kulon Progo, Yogyakarta - Arvendi Rachma Jadi; Hery Wijayanto; Dwi Liliek Kusindarta; Vista Budiariati; Tri Wahyu Pangestiningsih; Teguh Budipitojo; Ariana; Hevi Wihadmadyatami (Fakultas Peternakan Universitas Papua, 2022)
ABSTRACT The problem faced during the new normal period of the Covid-19 pandemic for students is to restore interest in learning that has been done at home. Additional efforts are needed to reduce these concerns, such as mentoring for learning outside of school. Community service in the form of learning assistance is carried out with the aim of providing new experiences, information, and knowledge outside of learning at school. The schools participating in the service activities are schools from Cluster VI Tuksono Village, Sentolo, Kulon Progo, Yogyakarta. This activity involves student assistants from the Anatomy Department, Faculty of Veterinary Medicine, Universitas Gadjah Mada with assistance for a certain period. Implementation of online activities providing materials and discussions that have been adapted to the competencies needed in schools. The material given is an introduction to vertebrates macroscopically and microscopically. Students will be divided into several classes and each has an assistant and a co-lecturer. The activity takes place from September to November 2021. The results of the questionnaire show that this learning assistance activity is very interesting (60%) and very useful (69%) for students and teachers in their schools. Keywords: Animal, Biology Anatomy; Elementary school; Learning; Online ABSTRAK Permasalahan yang dihadapi pada masa normal baru pandemi Covid-19 bagi peserta didik adalah mengembalikan minat belajar yang selama ini dilakukan di rumah. Usaha untuk mengurangi keprihatinan tersebut diperlukan seperti pendampingan belajar luar sekolah. Pengabdian kepada masyarakat berupa pendampingan pembelajaran dilaksanakan dengan tujuan memberikan pengalaman, informasi, dan pengetahuan baru di luar pembelajaran di sekolah. Sekolah yang berpartisipasi dalam kegiatan pengabdian adalah sekolah-sekolah dari Gugus VI Desa Tuksono, Sentolo, Kulon Progo, Yogyakarta. Kegiatan ini melibatkan asisten mahasiswa Departemen Anatomi Fakultas Kedokteran Hewan Universitas Gadjah Mada dengan pendampingan selama periode tertentu. Pelaksanaan kegiatan daring pemberian materi dan diskusi yang sudah disesuaikan dengan kompetensi yang dibutuhkan di sekolah. Materi yang diberikan berupa pengenalan vertebrata secara makroskopik dan mikroskopik. Peserta didik akan dibagi menjadi beberapa kelas dan masing-masing memiliki satu asisten dan dosen pendamping. Kegiatan berlangsung dari bulan September sampai November 2021. Hasil kuisioner menunjukkan kegiatan pendampingan pembelajaran ini sangat menarik (60%) dan sangat bermanfaat (69%) bagi para peserta didik dan guru di sekolahnya. Kata kunci: Anatomi Biologi; Daring; Hewan; Pembelajaran; Sekolah Dasar